2017
DOI: 10.1021/acs.analchem.6b03058
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Energetic Epitope of an Antibody/Interleukin-23 Interaction with Hydrogen/Deuterium Exchange, Fast Photochemical Oxidation of Proteins Mass Spectrometry, and Alanine Shave Mutagenesis

Abstract: Epitope mapping the specific residues of an antibody/antigen interaction can be used to support mechanistic interpretation, antibody optimization, and epitope novelty assessment. Thus, there is a strong need for mapping methods, particularly integrative ones. Here we report identification of an energetic epitope by determining the interfacial hot-spot that dominates the binding affinity for an anti-IL-23 antibody by using the complementary approaches of hydrogen/deuterium exchange mass spectrometry (HDX-MS), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 59 publications
0
78
0
Order By: Relevance
“…We also showed that FPOP reveals fast fluctuations occurring remotely upon ligand binding, which is undetectable by slower footprinting methods 24 . Thus, we applied FPOP as a probe with high sensitivity to monitor changes in structure and dynamics of IL-6R.…”
Section: Resultsmentioning
confidence: 64%
“…We also showed that FPOP reveals fast fluctuations occurring remotely upon ligand binding, which is undetectable by slower footprinting methods 24 . Thus, we applied FPOP as a probe with high sensitivity to monitor changes in structure and dynamics of IL-6R.…”
Section: Resultsmentioning
confidence: 64%
“…Footprinting results show an overlap of important epitope regions detected by HDX-MS and FPOP. These results demonstrate FPOP and HDX-MS are equally useful for epitope structural mapping (78). In additional studies, FPOP, HDX-MS, and GEE labeling were used in tandem to demonstrate that the critical binding epitope of the IL-6/IL-R complex is the short segment 135 QNSPAED 141 .…”
Section: Comparison Of Protein Footprinting Methods Used To Study Higmentioning
confidence: 87%
“…For example, by using HDX-MS, FPOP, alanine shave mutagenesis (i.e. mutating potential key residues into alanine to study their effect on protein structure and functionality), and binding analytics in tandem, Li et al (78) reported the identification of an energetic epitope by determining the interfacial hot spot that dominates the binding affinity for an anti-interleukin-23 (anti-IL-23) antibody (Fig. 3).…”
Section: Comparison Of Protein Footprinting Methods Used To Study Higmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (55)(56)(57)(58). For the labeling studies, PB10 was at 2-fold molar excess relative to RiVax to favor complex formation.…”
Section: Hx-ms Analysis Of Rivax Bound To Cluster I Mabs (Pb10 R70 mentioning
confidence: 99%